Comparison of dermatoscopic images of acral lentiginous melanoma and acral melanocytic nevus occurring on body weight-bearing areas - Watanabe, Soko; Sawada, Mizuki; Ishizaki, Sumiko; Kobayashi, Ken; Tanaka, Masaru (Dermatology Practical & Conceptual, 2014)
Background: Because body weight-bearing produces a shift in the horny layer, acral melanocytic nevus on the body weight-bearing area of the sole showed a regular fibrillar pattern (FP) due to slanting of the melanin columns in the horny layer. On the other hand, acral lentiginous melanoma (ALM) on the body weight-bearing area of the sole tended to show irregular fibrillar pattern showing rather structureless pigmentation instead of a parallel ridge pattern, which is due to the shift of the horny layer. Objective: To elucidate the subtle difference between the regular FP of nevus and irregular FP in ALM. Methods: In this study, the dermatoscopic features of five cases of ALM and five cases of acral melanocytic nevus on the weight-bearing area of the sole were compared. Results: All the cases with nevi showed regular FP showing regular distribution of fibrils, whereas all the melanomas showed irregular distribution of fibrils and colors. Fibrils in nevi tended to be clear at the furrows and dim at the ridges. White fibrils corresponding to the eccrine ducts in the horny layer were more often present on the ridges in ALM, which showed negative FP. Conclusion: Differentiating between the regular and irregular FP, including negative FP, might be helpful for the discrimination of melanoma from nevus.